2014
DOI: 10.1103/physrevb.89.054423
|View full text |Cite
|
Sign up to set email alerts
|

Domain wall pinning in notched nanowires

Abstract: We theoretically and numerically study magnetic domain wall (DW) pinning at a notch in a magnetic nanowire. Based on the static DW equation, a general relationship between an external field and a DW structure for a given notch geometry is found. By estimating the field below which this relationship holds, we obtain the depinning field theoretically. Our theoretical estimate of the depinning field compares well with simulation results. Furthermore, our theory explains well why the depinning field of a transvers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(32 citation statements)
references
References 35 publications
1
31
0
Order By: Relevance
“…As the notch depth increases, the pinning field increases, in agreement with the trend seen in Ref. 11. For a given notch depth, the rectangular notch has a higher pinning field than the triangular notch in wires that are 45 nm and 60 nm wide, but the difference is smaller in 30-nm-wide wires.…”
Section: -4 Dutta Et Alsupporting
confidence: 76%
See 1 more Smart Citation
“…As the notch depth increases, the pinning field increases, in agreement with the trend seen in Ref. 11. For a given notch depth, the rectangular notch has a higher pinning field than the triangular notch in wires that are 45 nm and 60 nm wide, but the difference is smaller in 30-nm-wide wires.…”
Section: -4 Dutta Et Alsupporting
confidence: 76%
“…Studies have shown the effect of LER on DW depinning in both in-plane magnetic anisotropy (IMA) and perpendicular magnetic anisotropy (PMA) nanowires. [6][7][8][9][10][11] A DW can also be pinned by local variations in anisotropy, which can arise from misorientation between grains in a polycrystalline film or from other perturbations in the nanowire anisotropy, due to inhomogeneous strain for example. 7,12 On the other hand, LER can facilitate the nucleation of a DW or the confinement of a DW to a region within the nanowire, which can be useful in device applications.…”
Section: Introductionmentioning
confidence: 99%
“…Creating structural defects were proposed to generate a potential well that acts as a pinning site for the DW. [9][10][11][12][13][14] The local modification of magnetic properties by ion implantation is a promising way without geometric constrictions to create pinning sites, which opens the possibility to achieve higher data-storage density. 15,16 However, the possibility of high density bit and successive bit-shift current density margin in such devices has not been sufficiently discussed yet.…”
Section: Introductionmentioning
confidence: 99%
“…5,4,8 When a DW in the nanowire is moving towards such a notch, the DW minimizes its energy by settling down in the notch in case of no external fields. 8,9 The energy to overcome the barrier of the notch can be supplied by the Zeeman energy of external fields 10,11 and is given by…”
Section: A Domain Wall Pinning At Notchesmentioning
confidence: 99%
“…4 The inherent nonvolatility of the magnets in pNML and the pipelined signal processing between logic gates according to a clocking field makes pNML suitable to a wide range of architectures and signal processing. 5,6 Generally, in digital logic circuits signals are transmitted, synchronized and buffered to facilitate complex logic circuitry. In pNML, usually nanowires with perpendicular magnetic anisotropy (PMA) are used as interconnects to transfer and control signals.…”
Section: Introductionmentioning
confidence: 99%